2020
DOI: 10.1016/s2215-0366(19)30510-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychological interventions for common mental disorders in women experiencing intimate partner violence in low-income and middle-income countries: a systematic review and meta-analysis

Abstract: Background Evidence on the effectiveness of psychological interventions for women with common mental disorders (CMDs) who also experience intimate partner violence is scarce. We aimed to test our hypothesis that exposure to intimate partner violence would reduce intervention effectiveness for CMDs in low-income and middle-income countries (LMICs).Methods For this systematic review and meta-analysis, we searched MEDLINE, Embase, PsycINFO, Web of Knowledge, Scopus, CINAHL, LILACS, ScieELO, Cochrane, PubMed datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 37 publications
1
64
0
2
Order By: Relevance
“…Moreover, gender-based violence is highly prevalent in South Asian countries [ 94 , 95 ]. Previous research has shown tremendous impacts of oppression and violence on women's psychosocial health [ 93 , 95 , 96 ]. Recent reports suggest a growing burden of domestic violence, which is likely to affect the mental health and wellbeing among South Asian women [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, gender-based violence is highly prevalent in South Asian countries [ 94 , 95 ]. Previous research has shown tremendous impacts of oppression and violence on women's psychosocial health [ 93 , 95 , 96 ]. Recent reports suggest a growing burden of domestic violence, which is likely to affect the mental health and wellbeing among South Asian women [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…Psychological interventions in women ­disclosing partner violence (improved ­anxiety but not depression) 153 ***…”
Section: Evidence Supporting Primary Prevention and Mental Health Promentioning
confidence: 99%
“…Funding: UK National Institute for Health Research ASSET and King's IoPPN Clinician Investigator Scholarship.”168…”
Section: Introductionmentioning
confidence: 99%
“…Future research should investigate whether adapting evidence-based psychological interventions for CMDs to address intimate partner violence enhances their acceptability, feasibility, and effectiveness in LMICs.Funding: UK National Institute for Health Research ASSET and King's IoPPN Clinician Investigator Scholarship. "168 amid personal protective equipment (PPE) shortages. Any recommendations about social or physical distancing, and the use of face masks, should be based on the best available evidence.…”
mentioning
confidence: 99%